THE IMPLEMENTATION OF LEADERSHIP ROLE IN IMPROVING MANAGERIAL SKILL OF CRAFTSMEN IN UPT ANEKA INDUSTRI DAN KERAJINAN SURABAYA - YULITA AYU WERDHANINGRUM, PUTU (Language Horizon: Journal of Language Studies, 2013)
Putu Yulita Ayu Werdhaningrum D3 – Business English, Faculty of Languages and Arts, University State of Surabaya, hyoelita@yahoo.co.id Abstract UPT Aneka Industri dan Kerajinan Surabaya is a technical services unit that can carry out the promotion and development of SMEs and Human Resources through technical training in the field of management, technology, process, production, standardization, environmental, and information. UPT Aneka Industri dan Kerajinan Surabaya has the aim to improve the performance of the technical implementation of various industrial units and crafts as well as developing human resource to support the competitiveness of the global market. In support of all the aim of the UPT, the researchers looked at the role of leadership to participate in the process of developing the performance of the craftsmen. Therefore, researchers are trying to see and understand firsthand how the leadership role to improve the performance of the craftsmen and what the response generated afterwards. Through the process of making this final assignment, the author can know that leadership is very supportive to improve the performance of the craftsmen. And by conducting job training, participated in various exhibitions, and provide counseling and guidance on a variety of crafts has given quite satisfactory results for the craftsmen in preparation to launch a new world in opening a small business and can also be one way to reduce unemployment in Indonesia. Keywords: Leader, Managerial Skill, Craftsmen. Introduction High unemployment in Indonesia, including the city of Surabaya. It then becomes a reference for policy actors seek alternative employment for others to absorb the available labor. Entrepreneurship is one alternative that can provide solutions to these problems. As of 2009, the number of unemployed in Indonesia as many as 3.713 million people, higher than the desired target of government at the level of 2.38 million people (Kompas, 2009). In addition, until 2007, there were 740,206 unemployed college graduates. This proves that the field work in Indonesia is very small while the number of graduates each year continues to grow, Eddy Suryanto Soegoto, 2010. Entrepreneurship in the goods sector is economic artery in big cities like Surabaya. The high increase of population, resulting in the need for goods is also increasing rapidly. The problem becomes more complex due to the time available did not allow the public to be able to do all the priority needs at once. Bids will need items that instantly becomes an option. According Ritonga (2011), unemployment is mainly due to the problem of unskilled labor and skilled. The company prefers candidates who already have the skills or expertise. The issue is very relevant in our country, given the large numbers of unemployed are people who do not have the skills or expertise. The causes of unemployment are very visible from the complaint that the lack of skills in a person. The lack of confidence in one’s soul, lack of interest and lack of socializing with others is also very influential in the intensity rising unemployment. It also agrees with Drs. Sudrajad, MM. (2011) who said "Cause Unemployment in Indonesia is the lack of desire to work, lack of skills and have thoughts just want to be an employee." This should be addressed with all efforts possible, because the average company today want and need employees who have the skill and expertise. Strengthening small and medium business sector is one of Indonesia’s development policy. SMEs have the ability to survive in times of economic crisis gripping the country. At great effort faltered storm knocked down the financial crisis, the SME sector is able to give breath to the nation’s economy. On this basis then arise initiative on craftsmen, to be able to meet those needs, by following the guidance and development by implementing the rules or ordinances of a leader who is really to improve the performance skills of a craftsman and judge it as something that is fairly decent to undertake entrepreneurial activities. Therefore, this is the reason why the researcher write about the efforts of a craftsman in business by implementing the rules of a good leader to improve their skills. In this case why the writer discuss this issue in order to make a useful input for all beginner craftsmen in Indonesia in order to become a successful craftsman and can open their own business field and in order to reduce the value of unemployment in Indonesia, especially in Surabaya. In the discussion of this material writer took guidance on UPT Aneka Industri dan Kerajinan Surabaya. Because according to the writer here is one of the features of a good government and the right to develop one’s own skills to become a craftsman by implementing the rules of a successful leader as well. And in this case, the craftsmen also want to improve the quality and quantity of a craftsman in Indonesia. And with the application is expected to be more able to produce more young craftsmen who are talented and can create new business field and to reduce unemployment in Indonesia. By conducting training to improve the skills of a person more likely to get jobs than those who do not. This is because companies prefer to hire people with the skills, so do not bother to practice again. And can even be a great opportunity to expand the opening of a new business pitch. This is also one way to overcome the educated unemployment is mostly done by the government, AnneAhira (Social and Cultural Rights, 2012). Based on the research, the objective of the study are : To describe the implementation of leadership role, To implementation of leadership role of the craftsman, To analyze the craftsmen respond after the implementation of leadership role. The researcher hopes this study can give contribution to the student, craftsmen, University, the institution and for the readers. For the student it can be provide new insights about the real world of work to students in the field of trade and industry and can prepare themselves before entering the world of work firsthand. For the Craftsmen to be a reference to become a successful entrepreneur by implementing the rule of a leader. For the University as input to evaluate the Extend to which the curriculum has been implement in accordance with requirements of skilled manpower in the field. For the Institution as a media to open up new business opportunities as an example for students. For the Readers can provide the information needed by the reader. Definition of Leadership Leadership is a person or a leader who can build the subordinates especially in this case is a craftsman to craftsmen to become a more developed and has a broad view of creativity in him. By applying the concepts and meaning of fostering a craftsman can be expected to be a key new birth craftsmen talented and have high creativity. A leader in this regard should be always trying to develop the talents of the craftsmen gradually and regularly which lead to the desired goals or objectives. Leaders and leadership can be approached from different angles (Thoha, 1986:3). Each approach will bear different meanings with other approaches. Leaders and leadership needed by humans due to the advantages and disadvantages possessed by each human being. The leader is a person who has certain skills that can influence their followers to cooperate towards the achievement of predetermined objectives. The ideal leader is a dream for every person, because that’s what leaders will bring forward-pullback of an organization, institution, company, state and nation. Surely the soul of a leader must have good soul of leadership that has been described in the above basic concepts and leadership should not be viewed as a facility for control, but meant as a sacrifice that must be carried out as well as possible. Leadership is also not arbitrary to act, but the power to serve and protect and do the fairest. Miftha Thoha in his book Organizational Behavior (1983:255) leader is someone who has the ability to lead, it means having the ability to influence another person or group without regard to the form of reason. Kartini Kartono (1994:33) the leader is a person who has the skills and strengths in particular skills and strengths in one area, so he was able to influence others to jointly carry out certain activities, for the achievement of one or more goals. Concept of Leadership The basic concept of the soul of leadership by Mr. Athoenk’s (2010): Leadership is a force that flows in a way that is not known to the leader of the disciples, encouraging his followers to be mobilized on a regular basis to the point that formulated. Working towards goals and achievements provide satisfaction for leaders and followers. Leadership is also coloring and colored by the place, the environment and climate in which it serves. Leadership does not work in an empty room, but the atmosphere created by the various elements. Leadership is always active, it could change in rank, intensity and extent. Leadership works according to the principles, tools and methods are defined and fixed. Leadership Function According to Yuki (1998) the function of leadership is trying to influence and direct the employees to work hard, have high morale and high motivation to achieve organizational goals. This is primarily tied to the function of regulating the relations between individuals or groups within the organization. Craftsmen Subject (actor) and object in every handicraft industry development program. People who work to make craft items or people who have specific skills related to the craft. These items are not made by machines, but by hand so often called handicraft items. Craftsman is a professional who works consistently high quality, "as an actor he was a perfect craftsmen". Craftsmen create great skill in the manual arts. Craftsmen also called creator, which means people who grow or make or create things. The Relationship between Leadership and Craftsmen In this case the role of a leader is also very important and participate in fostering and development by conducting training and exhibitions the work of craftsmen. And may provide a strategy to cultivate the efforts of craftsmen. It is expected that the craftsmen also have the soul of a leader in developing a business. It is also stated by Ari Setiawanan (2011) in his personal blogger states "Leadership is the process of influencing or give examples of leaders to followers in an effort to achieve organizational goals. Natural way to learn leadership is to "do it in the workplace" with practices like apprenticeship in a skilled artist, craftsman, or practitioner. In this connection, the expert is expected as part of its role providing teaching / instruction ". Discussion about leaders and leadership as well as its influence on a craftsman in general explains how to be a good leader, and a style that suits the nature of leadership and what conditions need to be possessed by a good leader. Nevertheless it is still difficult to implement in full, so that in practice only a few leaders are able to perform well and the leadership to bring his followers to the desired state. The conclusion is that the performance can be improved either craftsmen, company or institution requires a good leader. Performance can be affected craftsmen of how leaders motivate, leadership style, giving implementation skills of the craftsmen, performance planning, and human resource management policies. Someone craftsmen who satisfied the leadership of the head or leader, will show a good attitude and strive earnestly perform their duties as the reciprocal of the leaders and organizations that have given him satisfaction. If the quality of work improved craftsmen, will have an impact on the quality of earnings in a personal effort to open his business. Leadership positive influence in improving the performance of craftsmen, craftsmen positive influence on the performance of the work of art. With so very obvious that the relationship between the two closely related and have a positive impact for both parties. RESEARCH METHODOLOGY Research activities will not regardless of where the data is the raw material of information to provide a specific description of the object of research. Data are facts collected by researchers for the purpose of solving the problem or answer the research questions. Research data can come from a variety of sources collected by using a variety of techniques during the course of the study. Based on the source, research data can be grouped into two types of data qualitative research and quantitative research data. In this research, entitled “The Implementation of Leadership Role in Improving Managerial Skill of Craftsmen in UPT Aneka Industri dan Kerajinan Surabaya“. Based on the question “How does the implementation of leadership role in improving managerial skill of craftsmen? And How does the craftsmen respond after the implementation of leadership role?” so this research used qualitative research. Qualitative data is data that collected by means of a process that saw the object of research. Such data over see the process rather than the result because it is based on a description of the process and not on mathematical calculations. Data collection techniques include observation, interviews, literature reviews, etc. It also agrees with Cahya Suryana (2010:115) which says the data is qualitative data in the form of words, not in the form of numbers. Qualitative data obtained through a variety of data collection techniques such as interviews, document analysis, the discussion focused or observations that have been set forth in the notes field (transcript). Other forms of qualitative data was obtained through shooting images or video recordings. In this research the researcher conducted research in UPT Aneka Industri dan Kerajinan Surabaya. UPT is Technical Services Unit are carrying out promotion and development of Small and Medium Industries (SMEs) and the Human Resources or business through Technical Training in the field of Management, Technology, Production Process, Standardization, Environment and Information. UPT Aneka Industri dan Kerajinan Surabaya is located on Jl. Pagesangan II / 38-42 Surabaya. In this place has two training rooms, each for a capacity of 40 people, has 10 bedrooms for 40 craftsmen, and other facilities provided. The writer believe this place highly qualified resource persons and trusted to get info on how the implementation of leadership role of the craftsmen to improve their performance and other info needed writer. In this case the implementation of leadership role is expected to improve the managerial skills of the craftsmen and to cultivate leadership skills and can teach it back to the new craftsmen later. In improving the performance of the craftsmen, the researcher often do see education and training, held an exhibition to the work of the craftsmen, and attend job training activities in the field of craft in UPT. Therefore the role of leadership is needed to manage and cultivate the managerial skills of the craftsmen. The role of leaders build skills one must master thriving. This is the next level of the management skills pyramid. Someone who must master personal development. This is the level of management skills, which shows the skills a person must master to be successful and show how management skills build on each other toward success. These are the basics that made ??the role of a leader for the management skill craftsmen: Plans Set Direct Control Motivation Conducting Training and Coaching The direct involvement of leader In this study the data of things that can be applied by craftsmen is the attitude of leadership, responsibility, caring and discipline. All that can be applied when crafting artisan training, opened the exhibition and even open their own craft business. Which was all the training can provide the knowledge and skills in the use of natural materials as craft materials. Preparing artisans to improve their skills through training and creative design products. Facilitate in developing its business so as to improve the competitiveness of products in the local and international markets. By implementing a leadership role in the managerial skill craftsmen are expected to increase knowledge of the design and color combination to make crafts. Craftsmen can transfer the new knowledge gained to other craftsmen and all those who would learn a new craftsmen. Craftsmen can be more creative in making other handicrafts. RESULT AND DISCUSSION This chapter will analyze the data that has been collected. The purpose of analyzing the data is to answer the questions of the researcher. As mentioned in the first chapter, “How does the implementation of leadership role in improving managerial skill of craftsmen?“ and “How does the craftsmen respond after the implementation of leadership role?”. The subject in this research are the craftsmen. From sources that the authors could have about ±30 craftsmen who are doing the implementation and development of skill. In this research the author prefers the craftsmen making plaiting and ceramic or gypsum. The Implementation of Leadership Role in Improving Managerial Skill of Craftsmen In this case the data subject can be applied by craftsmen is the attitude of leadership, responsibility, a sense of caring and discipline. All that can be applied when artisans craft training, opened the exhibition and even opened his own craft business. Which is the training it can provide all the knowledge and skills in the use of natural materials as craft materials. Preparing crafters to enhance the capabilities and skills through creative design products. Facilitate in developing its business so as to improve the competitiveness of products in the local and international markets. With the moral support and provide the necessary facilities, providing motivation, conduct training and job fairs for the efforts of craftsmen also a way to improve the performance of the leader of the craftsmen. Here are some ways to improve the performance of the craftsmen: Guide and cultivate prospective new employers that will be developed into an independent businessman. Given coaching or income. Given technical training. Examples given creative woven design, gypsum, and ceramics. Held the exhibition of the craftsmen. The purpose of these activities is intended to: Improve the skills of the craftsmen, To foster the craftsmen in order to thrive, That the craftsmen more creative, Can give entrepreneurs insight, To support the welfare and craftsmen, Fostering the craftsmen to be independent and get satisfactory results, Mental strengthen the craftsmen to become a successful entrepreneur, as a successful entrepreneur should require struggle and sacrifice. The Craftsmen Respond after the Implementation of Leadership Role Subject (actor) and object in every handicraft industry development program. People who work to make craft items or people who have specific skills related to the craft. These items are not made by machines, but by hand so often called handicraft items. Craftsman is a professional who works consistently high quality, "as an actor he was a perfect craftsmen". For craftsmen to apply leadership role to improve the managerial skills of the craftsmen is very important because it can help the craftsmen to be able to perform all the activities during the training on the craft. In this case that is the primary motivation is a craftsman wants to be a successful artisans, craft businesses can open and create new jobs to reduce unemployment in Indonesia. CONCLUSION AND SUGGESTION Conclusion The conclusion is that the performance can be improved either craftsmen, company or institution requires a good leader. Performance can be affected craftsmen of how leaders motivate, leadership style, giving implementation skills of the craftsmen, performance planning, and human resource management policies. Someone craftsmen who satisfied the leadership of the head or leader, will show a good attitude and strive earnestly perform their duties as the reciprocal of the leaders and organizations that have given him satisfaction. If the quality of work improved craftsmen, will have an impact on the quality of earnings in a personal effort to open his business. Leadership positive influence in improving the performance of craftsmen, craftsmen positive influence on the performance of the work of art. With so very obvious that the relationship between the two closely related and have a positive impact for both parties. Suggestion The expectations of the craftsmen is that welfare can be much better and can open their own business field by always applying a given leadership roles during a training run. And hopefully this research can be useful for readers to find the information they want to know about the craftsmen can add insight and knowledge. And also can make a new discourse about the craftsmen at UPT Aneka Industri dan Kerajinan Surabaya. REFERENCE Peraturan Gubernur Jawa Timur, 2008, Organisasi Dan Tata Kerja Unit Pelayanan Teknis Dinas Perindustrian Dan Perdagangan Provinsi Jawa Timur, Surabaya. UPT Aneka Industri dan Kerajinan Jawa Timur, 2012, Pembinaan dan Pengembangan Karyawan dan Pengrajin, Jawa Timur, Surabaya. Reh, F. John. 2009. Management Skill. About.com Guide Http//.www.geogle.com.Bisnis dan Kewirausahaan Qibtiyah, Mariyatul. 2008. “PENGEMBANGAN USAHA SENTRA PENGRAJIN BATIK”. Malang: UIN. Reh, F. John. 2009. Management Guide. About.com Guide. It’s retrieved from http://management.about.com/bio/F-John-Reh-229.htm http//.www.geogle. com.What is Leadership Drs. Sudrajad, MM. 2011. Kiat Mengentaskan Pengangguran dan Kemiskinan melalui Wirausaha. Bumi Aksara Athoenk’s. Mr. (2010) Konsep Jiwa Pemimpin / Leadership. http://athoenk46.wordpress.com/?s=konsep+jiwa+pemimpin Zahra. Fatimah. Opinion Blog Unemployment, 2012. Universitas Gunadarma: Jakarta. It’s retrieved from http://fzahrah.blogspot.com/ Smith. Nasuha. 2011. Teori Dasar Kepemimpinan. It’s retrieved from http://nasuhasmith13.blogspot.com/2011/03/teori-dasar-kepemimpinan.html Wiradi. Dewa. 2012. Definisi Kepemimpinan Menurut Para Ahli dan Dalam Beberapa Kamus Modern Elqorni. Ahmad. 2011. Definisi pemimpin dan kepemimpinan. Emzeth. 2010. Kriteria Seorang Pemimpin from http://www.emzeth.com/2010/11/kriteria-seorang-pemimpin-sejati.html#ixzz1u0ecM9K6 Bahrodin. Deby Putra. 2012. Arti seorang Pemimpin, from http://www.dputra.com/2012/02/arti-seorang-pemimpin.html Setiadi, MKEP. 2011. Konsep Kepemimpinan. Power Point: Jakarta. http://referensi-kepemimpinan.blogspot.com/